The Digital Learning Model to Enhance Students' Understanding and Interest in Learning: A Case Study at Cangkreng II Lenteng State Elementary School, Sumenep - Akbar, Guntur Muda Putra Ali; Prastowo, Andi; Susantin, Jamiliya (At-Tafkir, 2024)
Traditional learning models are often less effective in increasing elementary school students' interest in science and technology. The limitations of interactivity and visualization in traditional models encourage the need for digital-based learning innovations. This study aims to identify the impact of digital learning models on students' interest and learning outcomes in science subjects. The research used a qualitative approach with a case study method. The research subjects consisted of school teachers at Cangkreng II Lenteng Sumenep primary school. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman analysis model which includes data condensation, data presentation, and conclusion. The findings indicate that digital learning models have great potential in improving the quality of science learning in primary schools. The use of interactive media, simulations, and engaging visualizations can help students build a better understanding of abstract science concepts. This research contributes to developing digital learning theory by demonstrating the effectiveness of technology-based learning models in improving students' motivation and learning achievement. The implication for learning practice is the importance of integrating digital technology into the science learning process to create a more enjoyable and effective learning environment.